Sense of community and homeowner participation in housing management: A study of Hong Kong - Yung Yau (Urbani Izziv, 2010)
Lack of homeowner participation in housing management (free riding) has rendered the management of many apartment buildings in Hong Kong ineffective. Proper apartment-building management depends on the voluntary contributions of individual homeowners. Individual homeowners are likely to free-ride on the management efforts of others because they consider the benefits of good housing management to be common goods. Apart from incentives such as subsidies offered by public entities and stricter law enforcement against homeowners that neglect building care, researchers have claimed that communitarian solutions may also work to tackle housing-management problems. In particular, there has been growing interest in the use of social capital, which is regarded as an asset of trust, reciprocity and cooperation, to foster a participatory culture among individual property owners. Empirical study of whether social capital plays a necessary role in housing management has been lacking. This study examines the linkage between social capital and homeowner participation in housing management in Hong Kong. The findings of this study have significant policy and practical implications. In addition to financial incentives or disincentives, public administrators can work to build a sense of community to achieve sustainable management of the existing housing stock in Hong Kong.